2009
DOI: 10.1016/j.aquatox.2009.02.017
|View full text |Cite
|
Sign up to set email alerts
|

In vitro hepatic metabolism of 2,2′,4,4′,5-pentabromodiphenyl ether (BDE 99) in Chinook Salmon (Onchorhynchus tshawytscha)

Abstract: Polybrominated diphenyl ethers (PBDEs) are brominated flame retardants that persist in the environment and are present in geographically widespread fish species. PBDE concentrations can be particularly high in resident Chinook salmon (Onchorhynchus tshawytscha) in the Puget Sound, Washington. Although PBDE residues in salmon and other fish are often dominated by lower brominated congeners, these congeners are not produced commercially in the greatest quantity, suggesting bioaccumulation of the lower molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
73
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 40 publications
(45 reference statements)
6
73
0
Order By: Relevance
“…These compounds were initially considered as metabolites or by-products of anthropogenic PBDEs because of the similarities in their structure (Haglund et al, 1997;Marsh et al, 2006). Some in vivo and in vitro studies have reported the biotransformation of OH-BDEs from various PBDEs (Erratico et al, 2010;Hakk et al, 2009;Malmberg et al, 2005;Qiu et al, 2007;Stapleton et al, 2009) despite the absence of OH-BDE formation in other PBDE exposure experiments (Benedict et al, 2007;Browne et al, 2009;Stapleton et al, 2006;Wan et al, 2009). However, concentrations of detected OH-BDEs were markedly lower than PBDEs, with a conversion ratio of w3% (Erratico et al, 2010;Hamers et al, 2008;Malmberg et al, 2005;Stapleton et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds were initially considered as metabolites or by-products of anthropogenic PBDEs because of the similarities in their structure (Haglund et al, 1997;Marsh et al, 2006). Some in vivo and in vitro studies have reported the biotransformation of OH-BDEs from various PBDEs (Erratico et al, 2010;Hakk et al, 2009;Malmberg et al, 2005;Qiu et al, 2007;Stapleton et al, 2009) despite the absence of OH-BDE formation in other PBDE exposure experiments (Benedict et al, 2007;Browne et al, 2009;Stapleton et al, 2006;Wan et al, 2009). However, concentrations of detected OH-BDEs were markedly lower than PBDEs, with a conversion ratio of w3% (Erratico et al, 2010;Hamers et al, 2008;Malmberg et al, 2005;Stapleton et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although early embryonic development of red-eared sliders and snapping turtles is similar [42,43], species-specific differences are likely in enzymatic systems potentially responsible for differential capacities for debromination, as has been shown in fish exposed to BDE-99 [7,10]. Several studies of fish have shown debromination of BDE-99 to BDE-47 in carp, but other species such as Chinook salmon and rainbow trout demonstrate different reductive metabolite products and slower formation rates [6,7,9,10]. Deiodinase enzymes (DIs)-which are responsible for the removal of iodine atoms from thyroid hormones, resulting in activation or deactivation of the hormones-have been suggested as the primary enzymatic system for debromination of BDE-99 to BDE-47 in fish, particularly in carp [7,9,10].…”
Section: Discussionmentioning
confidence: 94%
“…McKernan et al [8] reported the presence of several PBDE congeners in the egg contents of several species of birds that had been injected with DE-71 but were not detected in the dosing solution or control eggs. Although early embryonic development of red-eared sliders and snapping turtles is similar [42,43], species-specific differences are likely in enzymatic systems potentially responsible for differential capacities for debromination, as has been shown in fish exposed to BDE-99 [7,10]. Several studies of fish have shown debromination of BDE-99 to BDE-47 in carp, but other species such as Chinook salmon and rainbow trout demonstrate different reductive metabolite products and slower formation rates [6,7,9,10].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations